2007
DOI: 10.1186/1746-1596-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Spindle cell tumors of the larynx are rare. In some cases, the dignity is difficult to determine. We report two cases of laryngeal spindle cell tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…[8] Previous immunohistochemical studies of cystic angiomyolipomas demonstrated positive staining of the subepithelial stroma with melanocytic markers (HMB-45 and Melan-A), estrogen and progesterone receptors and CD10. [7,8] Moreover, muscle staining with actin and desmin and cyst lining staining with pancytokeratin were also demonstrated. [7,8] Of the RCC marker antigens, such as inhibin, WT-1, c-kit (CD117), S-100 protein, and CK20, no positive staining was detected for any of the three components of the tumor (i.e., smooth muscle tissue, blood vessels and mature adipose tissue), and a low proliferative index value was detected according to Ki67 labeling.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…[8] Previous immunohistochemical studies of cystic angiomyolipomas demonstrated positive staining of the subepithelial stroma with melanocytic markers (HMB-45 and Melan-A), estrogen and progesterone receptors and CD10. [7,8] Moreover, muscle staining with actin and desmin and cyst lining staining with pancytokeratin were also demonstrated. [7,8] Of the RCC marker antigens, such as inhibin, WT-1, c-kit (CD117), S-100 protein, and CK20, no positive staining was detected for any of the three components of the tumor (i.e., smooth muscle tissue, blood vessels and mature adipose tissue), and a low proliferative index value was detected according to Ki67 labeling.…”
Section: Discussionmentioning
confidence: 93%
“…Among the published cases in the literature regarding cystic angiomyolipomas, no cases of malignant transformation have been reported on follow-up, even among patients who had received nephron-sparing surgery. [5][6][7] Thus, according to the published literature, cystic angiomyolipomas seem to have a benign disease course similar to classic angiomyolipomas. [5][6][7][8] The differential diagnosis of cystic angiomyolipomas involves distinguishing between mixed epithelial and stromal tumors (previously classified as cystic hamartomas of the renal pelvis, adult mesoblastic nephroma, or renal pelvic or cortical hamartomas), cystic nephroma, multilocular cystic renal cell carcinoma, liposarcoma and vascular malformations.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The presence of malignant osteoid production and careful exclusion of epithelial differentiation distinguishes primary osteosarcoma from carcinosarcoma/sarcomatoid carcinoma, some of which are well known to contain osteoid [8,[27][28][29][30][31][32][33]. Thompson et al [30] and Viswanathan et al [31] described the largest series of laryngeal spindle cell (sarcomatoid) carcinoma, of 187 and 103 cases respectively.…”
Section: Literature Review and Discussionmentioning
confidence: 99%